Aspectos produtivos, nutricionais e bioeconômicos de híbridos de milho para produção de silage - Neumann, M.; Leão, G. F.M.; Coelho, M. G.; Figueira, D. N. [UNESP]; Spada, C. A.; Perussolo, L. F. (Cordoba University Press (UCOPress), 2017)
The objective was to evaluate the productive, nutritional and bioeconomic aspects of six corn hybrids for silage: SG 6030 YG, LG 6036 PRO, LG 6038 PRO, BRAS 3010, PL 6880 and PL 1335. Regarding the productive aspect, there was a significant difference (p<0.05) between the materials, and the SG 6030 YG, LG 6036 PRO, LG 6038 PRO hybrids, had the highest dry biomass (29,457; 28,089 and 25,609 kg ha-1, respectively) and grains production (12,360; 11,426 and 11,405 kg ha-1, respectively). It can be seen, from the nutritional aspect that there were no statistical difference (p>0.05) among the silages of the hybrids evaluated for MM values, CP, ADF, HEM and TDN having averaged 1.78%, 6.03%, 28.86%, 27.11% and 67.42% DM, respectively. However, NDF values were lower for the LG 6038 PRO hybrids, SG 6030 YG and PL 6880 (54.92%, 54.13% and 54.04%, respectively). The hybrids which obtained the highest yields (LG 6038 and LG 6036 PRO PRO) also showed better bioeconomic results, with costs of R$ 48.56 and R$ 48.80 per ton of NM, respectively. Thus, the LG 6038 PRO, PRO LG 6036 and SG 6030 YG hybrid are recommended for silage in the central-southern region of Paraná.
Productive, nutritional and bioeconomical aspects of corn hybrids for silage
Keywords: Dry biomass; Stay green; TDN